(untitled) (Journal of Educational Sciences, 2018)
The question of training up the younger generation is one of the great goals that has been pursued for centuries in the history of mankind. Our work emphasizes the relevance of the issue of improving the quality of future generations in accordance with the requirements of modern informatization based on our national values and proverbs.. Proverbs and sayings, it is a unique way to give people energy, is the fruit of the centuries-old point of view, the mind of the Kazakh people and the legacy of generations. This article presents a structured model of nurturing a spiritually rich person with the help of proverbs and sayings. Respect, obedience, kindheartedness, patriotism, culture, diligence, generosity, humanity, respect for national values are all a spiritual value. The author considers the problems of education of the future generation on the basis of proverbs and sayings. Thus, calls on the fact that proverbs and sayings have a special place in the formation of a civilized one with a high progressive moral basis, developed all-round, adapted to various social changes, consciously and qualitatively absorbing the knowledge, the spiritually rich personality of our generation, and it should be noted that the Kazakh people paid attention to the ethical-esthetic education of the person. It is also stated that the source of nationalist upbringing is the folk pedagogy of such enlighteners, as Y. Altynsarin, M. Zhumabayev and K.D. Ushinsky. And this is the core of folk wisdom. Key words: proverbs and sayings, upbringing, patriotic upbringing, spiritual values, folk pedagogy.